Validity and Reliability of the Richmond Agitation-Sedation Scale in Pediatric Intensive Care Patients: A Multicenter Study - Tapia, Rocío; López-Herce, Jesús; Arias, Ángel; del Castillo, Jimena; Mencía, Santiago (Frontiers in Pediatrics, 2022)
Background: There are limited data about the psychometric properties of the Richmond Agitation-Sedation Scale (RASS) in children. This study aims to analyze the validity and reliability of the RASS in assessing sedation and agitation in critically ill children. Methods: A multicenter prospective study in children admitted to pediatric intensive care, aged between 1 month and 18 years. Twenty-eight observers from 14 PICUs (pediatric intensive care units) participated. Every observation was assessed by 4 observers, 2 nurses and 2 pediatric intensivists. We analyzed RASS inter-rater reliability, construct validity by comparing RASS to the COMFORT behavior (COMFORT-B) scale and to a numeric rating scale (NRS), its ability to distinguish between levels of sedation, and responsiveness to changes in sedative dose levels. Results: 139 episodes in 55 patients were analyzed, with median age 3.6 years (interquartile range 0.7-7.8). Inter-rater reliability was excellent, weighted kappa (κw) 0.946 (95% CI, 0.93 – 0.96; p<0.001). RASS correlation with COMFORT-B scale, rho = 0.935 (p<0.001) and NRS, rho = 0.958 (p<0.001) were excellent. The RASS scores were significantly different (p<0.001) for the 3 sedation categories (over-sedation, optimum and under-sedation) of the COMFORT-B scale, with a good agreement between both scales, κw 0.827 (95% CI, 0.789 – 0.865; p<0.001), κ 0.762 (95% CI, 0.713-0.811, p<0.001). A significant change in RASS scores (p<0.001) was recorded with the variance of sedative doses. Conclusions: The RASS showed good measurement properties in PICU, in terms of inter-rater reliability, construct validity, and responsiveness. These properties, including its ability to categorize the patients into deep sedation, moderate-light sedation, and agitation, makes the RASS a useful instrument for monitoring sedation in PICU.